ANALISIS FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMILIHAN PERGURUAN TINGGI SWASTA (Studi Pada Politeknik Perdana Mandiri Purwakarta) - Dewi Puspasari (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
Referring to the standards or parameters of quality education, namely Government Regulation (PP) No.19 of 2005, there are eight standards that must be considered in order to realize quality education, namely content standards, process standards, competency standards, facilities and infrastructure standards, management standards, financing standards. and educational assessment standards. So education must now be managed professionally because campuses that do not have competitiveness will experience the impact of intense competition, namely the decline in the number of students. Campuses that can compete with other campuses are those that can promise a reputation/quality of quality education, facilities and infrastructure to support lectures, provide job opportunities after graduation, have varied study programs so that students can choose areas of concentration according to their talents and interests. This study aims to determine the factors that influence student decisions in choosing a college. This study uses quantitative research methods using primary data obtained from the results of the questionnaire. The subjects in this study amounted to 132 students of the Perdana Mandiri Polytechnic Purwakarta by using a sampling technique, namely proportional random sampling. Hypothesis testing using multiple linear regression analysis by calculating the t test, f test and test the coefficient of determination. The results of this research are the influence of Brand Image (X1), Campus Facilities (X2) and Campus Marketing factors (X3) on the Decision to Choose Higher Education (Y) which is 60.6%, the remaining 39.4% is influenced by other factors not examined in this study. Keywords : brand image, facilities, marketing, choose decisions.